Resource utilisation among patients with syncope presenting to the emergency department. Issue 6 (4th March 2021) - Lombardi, Kevin; Ong, Justin; Kane, Erin; Aljohani, Bandar; Frasure, Sarah E.; Almulhim, Khalid; Pourmand, Ali
Abstract: Background: Syncope is a common problem encountered in the emergency department (ED) and a significant source of ED resource utilisation, including advanced imaging modalities. Current guidelines do not recommend routine Computed Tomography (CT) imaging of the head for patients seen in the ED due to syncope. Objective: In this study, we investigate resource allocation in the ED for syncope‐related visits, including advanced imaging modalities using a large national database. Outcomes analysis: Data from the CDC's National Hospital Ambulatory Medical Care Survey (NHAMCS) for years 2008‐2017 were compiled and analysed. Intrinsic survey and constructed variables were utilised to identify and investigate all syncope‐related ED visits in the United States during the study period that met study criteria. Appropriate bivariate and multivariate statistical analyses were applied in order to identify and compare the resource utilisation, demographics, and ED visit dynamics of syncope and non‐syncope‐related ED visits. Results: During the study period, there were over 15 million ED visits for syncope. A high percentage of syncope visits received head CT compared with non‐syncope visits (34% vs. 4.5%, P  > .001). When investigated by age‐grouping utilisation of head CT ranged from 26.5 (95% CI 18.9‐27.5) for ages 18‐40 to as high as 40.2% (95% CI 33.8‐47.1) for ages 80 and higher. Compared with non‐syncope ED visits, syncope‐related ED visits were older and more likely to have Medicare or private insurance. Conclusion: Syncope continues to be a large and growing share of visits to US EDs. Despite well‐supported, evidence‐based recommendations that do not recommend routine utilisation of head CT in syncope‐related ED visits, these data suggest that emergency physicians routinely over‐utilise this modality. More specific guidelines may be required to help reduce the use of imaging studies for patients who present to the ED with syncope.